Emerging Technologies and Museums: Mediating Difficult Heritage - (:unkn) unknown (My University, 2022)
How can emerging technologies display, reveal and negotiate difficult, dissonant, negative or undesirable heritage? Emerging technologies in museums have the potential to reveal unheard or silenced stories, challenge preconceptions, encourage emotional responses, introduce the unexpected, and overall provide alternative experiences. By examining varied theoretical approaches and case studies, authors demonstrate how “awkward”, contested, and rarely discussed subjects and stories are treated – or can be potentially treated - in a museum setting with the use of the latest technology.
Keywords: Museums; Technology; Museum studies; Heritage studies; Media studies